Roseldorf Rekonstruiert - Jan Olofsson (EXARC Journal, 2012)
This review concerns the article "Roseldorf rekonstruiert – Ein keltischen Heiligtums entsteht in Asparn an der Zaya" published in EuroREA 6/2009.